Pembinaan Pelatihan Pembukuan Sederhana Dan Pemasaran Secara Digital Sesuai Pasal 1 Angka 26 UU KUP Pada UMKM Di Kabupaten Belitung - Dini Oktariani; Tsulis Amiruddin Zahri; Darus Altin; Dony Yanuar (Universita Bangka Belitung, 2022)
Micro, Small and Medium Enterprises (MSME) is aneconomic sector that has a large enough role in the nationaleconomy. The development of the number of SMEs from year toyear is increasing. The development of MSME in BelitungRegency has only been seen from the increasing number ofMSMEs, but financially only a few MSMEs have experienceddevelopment. One of the problems that often occurs by MSMEbusiness actors is about financial management for MSME in Kab.Belitung. The benefits of simple bookkeeping for MSME actorsare in terms of administration and ease of work for MSME actors.The reasons MSMEs do not use simple bookkeeping are, amongothers, considered something difficult and unimportant. SomeMSME actors said that without simple bookkeeping theirbusiness would still run smoothly. The target of this specialprogram is education through socialization about the mentoringprogram offered in the form of simple bookkeeping training forMSMEs. The bookkeeping taught is simple bookkeeping that isadapted to Article 1 number 26 of the KUP Law on conditions inMSME, but does not deviate from existing standards andregulations. This assistance is intended for MSMEs in BelitungRegency